(untitled) (Scientific journal of the Fergana State University, 2024)
The article examines some geographical aspects of the development of tourism and recreation within mountainous areas. Also, based on available theoretical and practical information, directions, conclusions and recommendations for the socio-economic development of mountainous areas are given.